Improving the Assessment of Solar Reflectivity of Exterior Aircraft Paints, and their Application Processes - Tremblay, Stephane (Université d'Ottawa / University of Ottawa, 2022)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed. À la demande de l'auteur, le résumé a été retiré en raison de la nature confidentielle de la thèse. Il sera ajouté une fois la période d'embargo terminée.
Keywords: Exterior; Paint